Cefiderocol therapy among immunocompromised adult patients: a descriptive analysis from a prospective, multicentre cohort study (Tufts University Tisch Library, 2025)
Keywords: Cefiderocol, Antibiotic therapy, Antimicrobial resistance, SOT, Mortality; Springer Open.